2000
DOI: 10.1016/s0002-9440(10)64992-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Analysis of the Human Prothrombinase Gene (HFGL2) and Its Role in Viral Hepatitis

Abstract: In the present studies, we report the cloning and structural characterization of the HFGL2 gene and its functional role in human fulminant hepatitis. The HFGL2 gene is approximately 7 kb in length with 2 exons. The putative promoter contains cis element consensus sequences that strongly suggest the inducibility of its expression. From the nucleotide sequence of the human gene, a 439-amino acid long protein is predicted. The overall identity between the murine fgl2 and hfgl2 coded proteins is over 70%. About 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
117
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 37 publications
11
117
0
Order By: Relevance
“…21,35,36 The results of this study clearly demonstrate that FGL2 is an important effector cytokine of Tregs that contributes to host susceptibility to MHV3-induced FH. Because we have shown that patients with FH and chronic HBV and hepatitis C virus infection have increased levels of FGL2, 30,37 the data presented here in concert with human studies suggest that measurement of FGL2 levels in the plasma may be useful in predicting the outcome of both experimental and human viral hepatitis and may provide a rationale for targeting FGL2 for the treatment of patients with acute and chronic viral hepatitis.…”
Section: Discussionmentioning
confidence: 62%
“…21,35,36 The results of this study clearly demonstrate that FGL2 is an important effector cytokine of Tregs that contributes to host susceptibility to MHV3-induced FH. Because we have shown that patients with FH and chronic HBV and hepatitis C virus infection have increased levels of FGL2, 30,37 the data presented here in concert with human studies suggest that measurement of FGL2 levels in the plasma may be useful in predicting the outcome of both experimental and human viral hepatitis and may provide a rationale for targeting FGL2 for the treatment of patients with acute and chronic viral hepatitis.…”
Section: Discussionmentioning
confidence: 62%
“…Given that Fgl2 is IFN␥-inducible (Figs. 1 and 2) and putatively contributes to fibrin formation (5,7,8), we evaluated T. gondii infection in Fgl2-deficient mice. In contrast to IFN␥-or fibrin-deficient mice, which succumb within 2 weeks of infection (12,27), Fgl2-deficient mice survived acute infection by strain ME49 T. gondii.…”
Section: Fgl2mentioning
confidence: 99%
“…Thus, despite its IFN␥ inducibility (Figs. 1 and 2) and putative procoagulant functions (5,7,8), Fgl2 expression is not required to survive the acute phase of T. gondii infection in mice, a model in which both IFN␥ and coagulation play critical protective roles (12,27).…”
Section: Fgl2mentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse fgl2 (mfgl2) and human fgl2 (hfgl2) have been localized to chromosomes 5 and 7, respectively (1-3). fgl2 prothrombinase has been shown previously to have the attributes of a serine protease capable of directly cleaving prothrombin to thrombin leading to fibrin deposition (2). Several studies indicate that mfgl2 is involved in experimental xenograft rejection by mediating "immune coagulation," fibrin deposition, and microthrombus formation, leading to classical pathological changes of acute vascular rejection (4).…”
mentioning
confidence: 99%